The Amazing Mathematical Beauty of the Mulatu Numbers With Interesting Open Questions - Mulatu, Lemma, (IJRDO -JOURNAL OF MATHEMATICS, 2018)
The Mulatu Numbers were introduced by Mulatu Lemma, Professor of Mathematics at Savannah State University.The numbers  are sequences of numbers of the form: 4,1, 5,6,11,17,28,45...  The numbers have wonderful and amazing properties and patterns.In mathematical terms, the sequence of the Mulatu numbers is defined by the following recurrence relation: In [1] and [2] some properties and patterns of the numbers were considered. In this paper, we investigate additional properties and patterns of these fascinating numbers. Many beautiful mathematical identities involving the Mulatu numbers in relation with the Fibonacci numbers and the Lucas numbers will be more explored. 2000 Mathematical Subject Classification:  11 Key Words: Mulatu numbers, Mulatu sequences, Fibonacci numbers, Lucas numbers, Fibonacci sequences, and Lucas sequences.